Application of high-velocity low-amplitude technique in cervicothoracic junction produces cardiovascular responses in subjects with C7-T1 dysfunction: Randomized crossover trial - Zago, Julio; de Souza, Bruna Urueña Lopes; Amatuzzi, Fellipe; Rondinel, Tatiana Zacarias; Queiroz, Rogério; Cipriano, Gerson; Cipriano, Graziela França Bernardelli (International journal of osteopathic medicine, 2023)
Neural structures of cardiac sympathetic and parasympathetic conduction emerge from the segments of the cervicothoracic spine. The application of high-velocity low-amplitude (HVLA) techniques at this segment can generate responses in heart rate (HR), blood pressure and sympathetic nervous activity of the skin. However, it is not known whether these responses occur in subjects with C7-T1 dysfunction. To evaluate the effects of HVLA technique in cervicothoracic junction in HR, blood pressure and skin temperature (ST), in subjects with C7-T1 dysfunction. This is a randomized crossover trial. Twelve male subjects were randomized into two groups: HVLA and Sham. HVLA group received a single manipulation technique for C7-T1 dysfunction, while the sham group received a simulated HVLA. HR, blood pressure and ST were measured pre, immediately after and 10 min after the application of the interventions. Immediately after the application of the interventions, an increase in HR, systolic blood pressure (SBP) and ST was observed, in addition to a reduction in diastolic blood pressure (DBP). Also, 10 min after, a significant reduction in SBP and DBP was observed in the HVLA group when compared to Sham group. The application of a single HVLA technique in the cervicothoracic junction produced significative effects on HR, BP and ST in subjects with C7-T1 dysfunction. ·This study showed that a musculoskeletal technique has effect on autonomic nervous system, suggesting that there are still hidden mechanisms behind HVLA techniques.·HVLA techniques for cervicothoracic junction can generate changes in cardiovascular variables.·HVLA techniques did not cause adverse hypertensive peaks. •This study showed an action of a musculoskeletal technique on the autonomic nervous system, proving that there are still hidden mechanisms behind HVLA techniques.•HVLA techniques for cervicothoracic junction can generate changes in cardiovascular variables, but not in an exacerbated way.•HVLA techniques did not cause hypertensive peaks, so we can consider them safe.